Counselling Persons with a Disability: A Professional Challenge - Westwood, Marvin J.; Nayman, Jeff (Canadian Journal of Counselling and Psychotherapy, 2012)
One of the key factors which should influence the direction of a counsellor education program is "client need". In this society there exists a significant number of people with disa- bilities for whom the process of personal and vocational adjustment requires the expertise of a counsellor with special training in rehabilitation. Unlike the United States, Canada does not have a graduate training program in rehabilitation counselling. The writers point out that such specialization in rehabilitation counselling can be developed with little diffi- culty within the existing graduate counsellor education programs ongoing in this country. Program development in training counsellors to work with clients with disabilities is a major challenge to counsellor education in Canada.